2017
DOI: 10.1109/ted.2017.2754248
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Source-Side Degradation of InAlN/GaN HEMTs Under High-Power Electrical Stress

Abstract: The electrical degradation of InAlN/GaN highelectron-mobility transistors (HEMTs) for millimeter-wave applications has been examined under simultaneous high VDS,stress and high IDstress electrical stress. Besides a drain current decrease and a positive threshold voltage shift, the creation of an anomalous source-side gate leakage path has been identified. We attribute this to high electric-field induced trap generation in the AlN layer directly under the gate edge on the source side. The resulting increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previously we have shown that under high-VDS-high-ID stress, significant degradation of the gate current takes place during the first few tens of seconds [2]. Additionally, we found that, unlike in conventional AlGaN/GaN devices where the barrier is relatively thick, the stress-induced leakage path appears on the source side [9]. This is unexpected particularly in light of conventional AlGaN/GaN HEMTs with a thicker barrier layer for which drain-side degradation dominates under similar stress conditions [10]- [12].…”
Section: Devices and Step-stress Experimentsmentioning
confidence: 69%
See 2 more Smart Citations
“…Previously we have shown that under high-VDS-high-ID stress, significant degradation of the gate current takes place during the first few tens of seconds [2]. Additionally, we found that, unlike in conventional AlGaN/GaN devices where the barrier is relatively thick, the stress-induced leakage path appears on the source side [9]. This is unexpected particularly in light of conventional AlGaN/GaN HEMTs with a thicker barrier layer for which drain-side degradation dominates under similar stress conditions [10]- [12].…”
Section: Devices and Step-stress Experimentsmentioning
confidence: 69%
“…This is unexpected particularly in light of conventional AlGaN/GaN HEMTs with a thicker barrier layer for which drain-side degradation dominates under similar stress conditions [10]- [12]. After analyzing the difference in terms of stress conditions on the source and drain sides, we postulated a defect formation degradation mechanism caused by high electric field across the 1 nm AlN layer on the source side together with high IGstress (through the source side) coupled with significant self-heating [9].…”
Section: Devices and Step-stress Experimentsmentioning
confidence: 96%
See 1 more Smart Citation